Enhanced Heat Transport Capability across Boron Nitride/Copper Interface through Inelastic Phonon Scattering. (27th July 2022) - Wang, Jingjing; Wang, Ziyang; Yang, Kunming; Chen, Naiqi; Ni, Jiamiao; Song, Jian; Li, Quan; Sun, Fangyuan; Liu, Yue; Fan, Tongxiang
Abstract: Interfacial thermal resistance plays a critical role in heat dissipation, when the mean free paths of heat energy carriers approach or exceed the characteristic lengths of devices. Deep understanding on electron and phonon scattering, as well as their coupling behaviors are of importance for interfacial heat transport enhancement. In this work, complicated influential mechanisms of interface defects on phonon scattering are studied, from the aspects of both time‐domain thermoreflectance (TDTR) measurements and atomistic simulations. Particularly, this study focuses on the comprehensive influence of inelastic phonon scattering on interfacial thermal conductance ( h K ) of hexagonal and amorphous boron nitride (BN)/copper (Cu) interfaces with nonreactive and nondiffusive features. The TDTR results imply that the h K of Al/a‐BN/Cu is ≈80% higher than that of Al/h‐BN/Cu counterpart, with the comparable film thicknesses, grain sizes, and interface roughness. Although lower local strain near h‐BN/Cu interface can boost electron–phonon coupling, inelastic phonon scattering at a‐BN/Cu interface may greatly promote the interfacial heat transport. The authors believe multiple phonons scattering accompanied by high‐frequency phonons transformation to low‐frequency phonons within a‐BN may provide more phonon–phonon coupling channels at the a‐BN/Cu interface. The present findings may provide more insights to understand nanoscale heat transport mechanisms at metal/nonmetal interfaces. Abstract : With the comparable film thickness, average grain sizes, and interface roughness, thermal boundary conductance of the Al/amorphous boron nitride (a‐BN)/Cu is ≈80% higher than that of the Al/hexagonal BN (h‐BN)/Cu. This is attributed to the inelastic phonon scattering accompanied by high‐frequency phonons transformation to low‐frequency phonons within a‐BN, which provides more phonon–phonon coupling channels at the a‐BN/Cu interface.